Research on Erection System of a Vehicle Missile. (August 2020) - Yang, Minbo; Ji, Yueyue; Ma, Cong; Wu, Qipeng
Abstract: The defects of existing erection system of a vehicle missile mainly include long erection time, large volume and poor adaptability to harsh environmental condition, so a new type of gas-fired electric erection system is designed. After the structure and working principle are introduced, the similar model of a missile is established according to the similarity theory. Through the analysis of the working process of the system, the mathematical model is established and the simulation model is also established by using Matlab / Simulink. Finally, the simulation analysis is carried out. The result shows that the erection system can achieve the quick erection of a heavy vehicle missile, which lays the foundation for the subsequent engineering application.